PENGARUH EFISIENSI DAN TRANSPARANSI TERHADAP KINERJA PERTUMBUHAN KABUPATEN BEKASI - Puji Waluyo (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
The purpose of this research was to determine the effect of efficiency and transparency variables on the growth performance of Kabupaten Bekasi. The results of the study found that there was a significant effect at the 5 percent significance level between the perception of partial transparency on growth performance in Kabupaten Bekasi. However, it is not significant on the efficiency and transparency variables. There is a significant effect at the 5 percent significance level between the perception of efficiency and transparency simultaneously on growth performance in Kabupaten Bekasi where the calculated F is greater than the F table at a value of 3.646. There is a dominant influence in transparency on perceptions of efficiency and transparency on growth performance in Kabupaten Bekasi.